THE ROLE OF PUBLIC-PRIVATE PARTNERSHIP IN THE DEVELOPMENT OF RAILWAY PASSENGER TRANSPORT SERVICES IN UZBEKISTAN: INTERNATIONAL EXPERIENCE AND RECOMMENDATIONS - Kudrat Shukhratovich Iskandarov (European Science Publishing, 2025)
The article presents an examination of foreign experience in creating and operating a management system for public-private partnership projects. The study presents the most successful practices in the development of public-private partnerships. The analysis of practical experiences in the domain of public-private partnerships led to the identification of the principal criteria for the success of public management systems for such projects. The identified criteria were then used to consider the possibilities of improving public-private partnership mechanisms in selected areas in the Republic of Uzbekistan. Furthermore, the implementation of public-private partnerships in the further development of the railway passenger transportation sector was contemplated.
Keywords: Public-private partnership; control system; passenger transportation by railway; railway stations; foreign management experience.